Preventing torture for people deprived of freedom: The Atlantic Hope and Black Swan Prison Model - Ogbozor, Ernest N.; Schoeny, Mara L.; Baer, Andrew E. (Torture Journal, 2017)
International law and minimum standards provide certain protection for detainees and prisoners of war (POW) against torture and ill-treatment. Places of detention and parties to conflicts are often monitored to ensure that they adhere to the required standards through, for example, visits to individual detainees and the assessment of facilities. However, monitoring between the point of arrest and eventual remand in prisons is largely inadequate. This paper explains an emerging model to enhance protection of prisoners through readiness training for prospective humanitarian personnel. The Atlantic Hope simulation exercise on monitoring detainees and visits to the mock Black Swan prison represents a teaching model to enhance sustainable protection of detainees and POW during incarceration. The simulation entails comprehensive monitoring, assessment, visits and provision of services to prisoners from the point of arrest, during the transition to places of custody, and imprisonment. These enhance protection of detainees to avoid deaths in custody, disappearance and torture throughout the chain of imprisonment.